NAVIGATING EQUITY CROWDFUNDING: INFORMATIONAL VS. RELATIONAL INFLUENCE ON INVESTOR BEHAVIOR - Zaenal Aripin; Ijang Faisal; Endang Ruchiyat (Organisasi Kreatif Indonesia Emas, 2024)
This research analyzes the interaction between informational and relational influences in investor behavior in choosing equity crowdfunding. This approach includes in-depth literature studies from various relevant sources such as scientific journals, books and research reports. Informational influence involves analyzing market data and financial information to evaluate a fund's performance and investment potential, while relational influence creates a subjective dimension in investment decision making, including trust, comfort, and loyalty. Research shows that a good relational relationship between investors and fund managers plays an important role in establishing investors' trust and comfort in choosing equity crowdfunding. Investors tend to trust fund managers they know and trust, even if market information shows signs to the contrary. Additionally, strong relationships also allow investors to gain easier access to relevant and useful information about the equity funds they are considering. However, the interaction between informational and relational influences is not always positive, as too strong a relationship can cloud an investor's objective assessment of a fund's performance or potential investment risk. Therefore, it is important for investors to strike the right balance between informational and relational influences in long-term investment decision making in equity crowdfunding. By paying attention to these aspects, investors can make more informed and sustainable investment decisions, which are in line with their long-term investment goals.